Analysis of quality of life among asthmatic individuals with obesity and its relationship with pulmonary function: cross-sectional study - Baltieri, Letícia; Martins, Luiz Claudio; Cazzo, Everton; Modena, Débora Aparecida Oliveira; Gobato, Renata Cristina; Candido, Elaine Cristina; Chaim, Elinton Adami (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: The combined effect of obesity and asthma may lead to significant impairment of quality of life (QOL). The aim here was to evaluate the prevalence of asthma among obese individuals, characterize the severity of impairment of quality of life and measure its relationship with pulmonary function. DESIGN AND SETTING: Observational cross-sectional study in public university hospital. METHODS: Morbidly obese individuals (body mass index > 40 kg/m2) seen in a bariatric surgery outpatient clinic and diagnosed with asthma, were included. Anthropometric data were collected, the Standardized Asthma Quality of Life Questionnaire (AQLQ(S)) was applied and spirometry was performed. The subjects were divided into two groups based on the median of the score in the questionnaire (worse < 4 and better ≥ 4) and were compared regarding anthropometric data and pulmonary function. RESULTS: Among the 4791 individuals evaluated, 219 were asthmatic; the prevalence of asthma was 4.57%. Of these, 91 individuals were called to start multidisciplinary follow-up during the study period, of whom 82 answered the questionnaire. The median score in the AQLQ(S) was 3.96 points and, thus, the individuals were classified as having moderate impairment of their overall QOL. When divided according to better or worse QOL, there was a statistically difference in forced expiratory flow (FEF) 25-75%, with higher values in the better QOL group. CONCLUSION: The prevalence of asthma was 4.57% and QOL was impaired among the asthmatic obese individuals. The worst QOL domain related to environmental stimuli and the best QOL domain to limitations of the activities. Worse QOL was correlated with poorer values for FEF 25-75%.